The UK Diabetes Research Network--an opportunity and a challenge. - Matthews, DR; Kennedy, E; Darbyshire, J; Johnston, D (2007)
The Department of Health has funded a national diabetes network to support clinical research. The network will facilitate recruitment into clinical trials and has been widely welcomed by clinicians. However, if the network is to reach its full potential, all those involved will need to advocate a change in attitude towards clinical trials and research, encouraging participation and contribution of data. Clinicians need to be willing to take a proactive view about research studies, and to encourage patients to adopt a positive and altruistic attitude towards trial participation. The future of trials and other important clinical research in the UK may depend on it.